The Blockade of Interleukin-2 During the Acute Phase of Trypanosoma cruzi Infection Reveals Its Dominant Regulatory Role - Nihei, Jorge; Cardillo, Fabiola; Mengel, Jose (Frontiers in Cellular and Infection Microbiology, 2021)
Trypanosoma cruzi infection causes Chagas' disease in humans. The infection activates the innate and adaptative immunity in an orchestrated immune response to control parasite growth, guaranteeing host survival. Despite an effective immune response to the parasite in the acute phase, the infection progresses to a chronic stage. The parasite infects different tissues such as peripheral neurons, the brain, skeletal muscle, and heart muscle, among many others. It is evident now that tissue-specific immune responses may develop along with anti-parasite immunity. Therefore, mechanisms to regulate immunity and to ensure tissue-specific tolerance are operating during the infection. Studying those immunoregulatory mechanisms is fundamental to improve host protection or control inflammatory reactions that may lead to pathology. The role of IL-2 during T. cruzi infection is not established. IL-2 production by T cells is strongly down-modulated early in the disease by unknown mechanisms and remains low during the chronic phase of the disease. IL-2 activates NK cells, CD4, and CD8 T cells and may be necessary to immunity development. Also, the expansion and maintenance of regulatory T cells require IL-2. Thus, IL-2 may be a key cytokine involved in promoting or down-regulating immune responses, probably in a dose-dependent manner. This study blocked IL-2 during the acute T. cruzi infection by using a neutralizing monoclonal antibody. The results show that parasitemia and mortality rate was lower in animals treated with anti-IL-2. The percentages and total numbers of CD4+CD25+Foxp-3+ T cells diminished within three weeks of infection. The numbers of splenic activated/memory CD4 and CD8 splenic T cells increased during the acute infection. T cells producing IFN-, TNF- and IL-10 also augmented in anti-IL-2-treated infected mice. The IL-2 blockade also increased the numbers of inflammatory cells in the heart and skeletal muscles and the amount of IL-17 produced by heart T cells. These results suggest that IL-2 might be involved in the immune regulatory response during the acute T. cruzi infection, dampening T cell activation through the expansion/maintenance of regulatory T cells and regulating IL-17 production. Therefore, the IL-2 pathway is an attractive target for therapeutic purposes in acute and chronic phases of Chagas' disease.